Intrapartum Asphyxiated Newborns Without Fetal Heart Rate and Cord Blood Gases Abnormalities: Two Case Reports of Shoulder Dystocia to Reflect Upon - Gina Ancora (Frontiers in Pediatrics, 2020)
Our report covers two cases of severe hypoxic-ischemic encephalopathy in newborns whose birth was complicated by shoulder dystocia. In both cases, there were inconsistencies observed among cardiotocographic traces, baby's clinical conditions at birth, and umbilical cord blood gases. Namely, normal cardiotocographic monitoring and cord pH > 7, in spite of the fact that the newborns were severely depressed at birth and their blood gases evaluated within 1 h from birth showed a severe metabolic acidosis. Moreover, one of the two newborns displayed moderately low hemoglobin levels. Metabolic and infectious causes were ruled out. Both newborns developed severe hypoxic-ischemic encephalopathy and received therapeutic hypothermia for 72 h. Both survived, one with a severe dystonic cerebral palsy whereas the other developed only a mild developmental delay in language. Cardiac asystole theory could explain these two cases, reinforcing the need for specific resuscitation guidelines for infants experiencing a birth complicated by shoulder dystocia.